CORRUPTION AS A PROBLEM OF INJUSTICE - Joe Jitek (Современная наука и инновации)
This article reviews existing scientific approaches to the corruption study such as political, economic, functional, and normative-values-based approaches.The political approach views corruption as the misuse of power by a public official for personal and/or group political gain, the solution to corruption is put forward to improve democratization.The economic approach regards the individual as a rational agent, and defines corruption as rationally selfish behavior with careful calculation. All individuals, including politicians and businessmen, commit corruption on selfishly rational calculations because the benefit of corruption is greater than the risk.The functional approach asserts the positive role of corruption in developing countries depending on the socio-cultural context. In this regard, in each society corruption is defined according to each sociocultural context.The author puts forward that the main task in the fight against corruption is to develop a «judgment criterion of corruption», according to which corruption can be defined and which does not fluctuate in each context. In this regard, the author first considers legal norms as a «judgment criterion of corruption» for a more consistent definition of corruption.According to the normative value approach, when discussing the «criterion» it is necessary to consider not only legal norms but also the «a tacit consent» of society. This approach additionally treats corruption as inappropriate behavior with tacit consent and suggests moral principles such as ethics, morality, goodwill and other similar values as the judgment criterion for corruption.However, in order to say that the «criterion of society's judgment» equals moralprinciples or a tacit consent, precise explanations must be provided as to what the values presented above are and whether they can serve as a «just criterion» regardless of any sociocultural context and time horizon.Considering the above approaches, the author concludes that for a true fight against corruption it is necessary to develop a «judgment criterion of corruption», which allows to identify the fundamental causes of corruption, to define its universal definition and to develop a coherent anti-corruption strategy.